2014
DOI: 10.1016/j.cell.2014.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide Mapping Reveals Widespread Dynamic-Regulated Pseudouridylation of ncRNA and mRNA

Abstract: SUMMARY Pseudouridine is the most abundant RNA modification, yet except for a few well-studied cases, little is known about the modified positions and their function(s). Here, we develop Ψ-seq for transcriptome-wide quantitative mapping of pseudouridine. We validate Ψ-seq with spike-ins and de novo identification of previously reported positions and discover hundreds of novel sites in human and yeast mRNAs and snoRNAs. Perturbing pseudouridine synthases (PUSs) uncovers which PUSs modify each site and their tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
1,074
5
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 827 publications
(1,183 citation statements)
references
References 57 publications
26
1,074
5
6
Order By: Relevance
“…On the order of 250 to 300 sites have now been mapped in yeast mRNA at single base resolution. [22][23][24] In human, the reported number of mRNA C sites varies widely from 96 in one study, 23 to 353 in a second, 22 and up to 2084 in a third study. 25 This variation is likely the result of technical differences in experimental design and data analysis.…”
Section: Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…On the order of 250 to 300 sites have now been mapped in yeast mRNA at single base resolution. [22][23][24] In human, the reported number of mRNA C sites varies widely from 96 in one study, 23 to 353 in a second, 22 and up to 2084 in a third study. 25 This variation is likely the result of technical differences in experimental design and data analysis.…”
Section: Mrnamentioning
confidence: 99%
“…In keeping with an emerging theme among mRNA modifications, however, C is dynamic in heat shock, nutrient deprivation, and other stresses. 22,23,25 While 5-methylcytidine (m 5 C) is best known for its central role as an epigenetic mark in DNA, it was also described in early studies of RNA methylation. 3 Mapping of m 5 C in RNA was initially attempted by adapting the bisulfite sequencing technology used for m 5 C in DNA, leading to the identification of approximately 10,000 m 5 C sites in mRNA.…”
Section: Mrnamentioning
confidence: 99%
“…Collectively, the papers by Carlile et al [3] and Schwartz et al [4] provide the first global detections of Ψ, and suggest potential regulatory functions of this modification in mRNA. Future research will focus on functional roles of Ψ, either through changing the RNA structure or recoding during translation.…”
mentioning
confidence: 95%
“…In the recent two papers, Carlile et al [3] and Schwartz et al [4] each reported a transcriptome-wide sequencing approach for mapping Ψ at single-base resolution. They both took advantage of the known reaction between Ψ and Ncyclohexyl-N'-(2-morpholinoethyl)carbodiimide metho-p-toluenesulphonate (CMC) to form N3-CMC-Ψ ( Figure 1B).…”
mentioning
confidence: 99%
See 1 more Smart Citation